2005
DOI: 10.1002/hep.20896
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in NASH: Postprandial Lipid Metabolism as a Link Between Adiponectin and Liver Disease *

Abstract: Circulating levels of four adipokines (adiponectin, TNF-␣, leptin, and resistin) and the postprandial lipid and adiponectin responses to an oral fat load were assessed in 25 nonobese, non-diabetic patients with biopsy-proven nonalcoholic steatohepatitis (NASH) and correlated with metabolic indices and liver histology. Circulating adiponectin was lower in NASH compared with controls (5,476 ؎ 344 vs. 11,548 ؎ 836 ng/mL; P ‫؍‬ .00001) and on multiple regression analysis correlated negatively with liver steatosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
155
2
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(184 citation statements)
references
References 48 publications
17
155
2
10
Order By: Relevance
“…Numerous studies have found that low APN is characteristic of fatty liver independently from IR and TNF-a (Hui et al, 2004;Musso et al, 2005a), the level of which was negatively correlated with liver steatosis, inflammatory necrosis, and fibrosis (Musso et al, 2005b). In T2DM, particularly in obese T2DM, plasma APN level also decreased significantly, which was negatively correlated with IR and hyperinsulinemia (Weyer et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have found that low APN is characteristic of fatty liver independently from IR and TNF-a (Hui et al, 2004;Musso et al, 2005a), the level of which was negatively correlated with liver steatosis, inflammatory necrosis, and fibrosis (Musso et al, 2005b). In T2DM, particularly in obese T2DM, plasma APN level also decreased significantly, which was negatively correlated with IR and hyperinsulinemia (Weyer et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Most children (95%) in this cohort were overweight or obese. They displayed metabolic characteristics typical of NAFLD (Patton et al, 2006;Roberts, 2007): insulin resistance with hyperinsulinemia; dyslipidemia; hypoadipoinectinemia (Musso et al, 2005;Gilardini et al, 2006;Nakayama et al, 2009). WC, as such or expressed as waist-height ratio, was increased in all but one child.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, adiponectin signalling alleviated or prevented NASH in mice, 33,34 and associations of hypoadiponectinaemia with fatty liver and/or NASH have been reported in humans. 35,36 Furthermore, genetic studies revealed associations of ADIPOR1/2 with IR and liver fat content, 37,38 and overexpression of ADIPOR1/2 has been shown to potentiate subeffective doses of adiponectin. 39 We therefore suggest that the increased ADIPOR1/2 mRNA expression in obese, insulin-resistant subjects represents a mechanism that may partially compensate for reduced plasma adiponectin.…”
Section: Discussionmentioning
confidence: 99%